DEFINING THE FUNCTIONS OF ANTI-CRISIS MANAGEMENT OF THE RUSSIAN ECONOMY - D. V. Manushin (Russian Journal of Economics and Law)
The work presents summary and evaluation of opinions of a number of researchers studying the functions of anti-crisis management; reveals and proves the functions of anti-crisis management in the Russian economy; defines and grounds the level of each function's significance.